Comparison of Retinal Nerve Fiber Layer Thickness Between Mild to Moderately Myopic Eyes with Normal Eyes - Raja Muhammad Taimoor Khan, Haroon Saleem, Shahid Anwar Bhatti, Muhammad Usman Sadiq, Muhammad Irfan Sadiq, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To access the difference between the mean thickness of the retinal nerve fiber layer (RNFL) in myopic eyes (down to -6.00 D) and the normal eye. Study Design: An Observational and Descriptive study. Place duration: In the department of Ophthalmology, Al Shifa Trust Eye Hospital, Rawalpindi for six-months duration from June 2020 to November 2020. Methods: In this study, the mean comparison of RNFL among 70 myopic eyes (down to -6.00 D) and 70 normal eyes of the same age was done. 15-45 years was the patients’ age range. A comprehensive eye exam was performed and thickness of RNFL was evaluated by optical coherence tomography. Data analysis was done with t-test for independent samples using SPSS 21.0; p <0.05 as the significant value. Results: The RNFL mean variation between both groups was 5.901 µm (SE: 1.930). The mean RNFL thickness in the group of people with myopia was 96.31 ± 11.121 µm with (SE: 1.310) and mean age was 28.32 ± 7.452 years. The mean thickness of RNFL was 94.210 ± 9.521 µm in the right eye and 99.175 ± 11.142 µm in the left eye. The RNFL mean score of thickness for eyes with myopia distributed normally as p <0.04. The RNFL mean score of thickness for normal group was (102.81 ± 11.48 µm) with (SE: 1.40), and the mean thickness of RNFL evaluated in healthy eyes did not show a normal distribution as P <0.20. This study outcomes exhibited a statistically substantial variance between the mean thickness of RNFL assessed in myopic and normal eyes (p <0.003). Conclusion: There is a significant variation in mean thickness of RNFL between normal and myopic eyes as assessed by optical coherence tomography. Appropriate understanding of data of RNFL in eyes with myopia is suggested to evade glaucoma misdiagnosis. Keywords: Optical coherence tomography, Myopia and Thickness of the Retinal Nerve Fiber Layer